Spatial Effects of Open Borders on the Czech Labour Market - Michael Moritz (Austrian Institute of Economic Research (WIFO), 2009)
Although it was barely analysed in the literature, the fall of the Iron Curtain also had effects on the regional structures of the labour markets in the Central and Eastern European Countries (CEECs). Focusing on the Czech Republic I analyse whether, during the undoubtedly increasing integration of markets, the Czech border region close to the Western European high-wage countries benefited from its geographical position. Even without transnational free labour mobility, free trade and outsourcing of production activities can lead to shifts in the labour demand and wage structure with respect to different skill groups. According to the theoretical background these integration effects should be stronger in border regions.
Keywords: 330; regional labour markets; border regions; international trade; employment; wage inequality; Regionaler Arbeitsmarkt; Marktintegration; EU-Binnenmarkt; Beschäftigungseffekt; Regionale Lohnstruktur; Grenzregion; Tschechien